FROM RIVERSIDE HUB TO URBAN CENTER: UNDERSTANDING THE METAMORPHOSIS OF THE SULTANATE OF DELI'S CAPITAL LANDSCAPE - Affan, Muhammad (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2023)
ABSTRACTThe Sultanate of Deli is a sultanate located on the east coast of Sumatra that has been colonized by the Dutch since 1862. Before colonization by the Dutch, the capital of the Sultanate of Deli was located in a riverside town called Labuhan. A few decades after colonization, the Sultan of Deli moved his capital to Sultangrond in Medan Putri. The move has led to significant changes in the role of the capital of the Sultanate of Deli. The following study aims to explain the changing role played by the capital of the Sultanate of Deli before and after the move. The results of the study are expected to contribute positively to knowledge about the history of sultanates in the archipelago. The method used in this study is the literature research method. The results of the study show that the sultanate capital in Labuhan played a more complex role than the capital in Sultandgrond. Labuhan not only served as the center of the Deli Sultanate's government but also as an economic center where the Deli export and import ports were also located. Meanwhile, after the move of the capital to Sultangrond in Medan, the capital of the Sultanate of Deli no longer played the role of an economic center as before.Keywords: Deli Sultanate, history of Islam, Labuhan, Sultangrond, East Coast of SumatraÂ ABSTRAKKesultanan Deli adalah sebuah kesultanan yang berada di kawasan Pantai Timur Sumatera yang dikolonisasi oleh Belanda sejak Tahun 1862. Sebelum di kolonisasi oleh Belanda, ibukota Kesultanan Deli berlokasi di sebuah kota tepian sungai yang bernama Labuhan. Beberapa dekade setelah kolonisasi, Sultan Deli memindahkan ibukotanya ke Sultangrond di Medan Putri. Pemindahan tersebut telah menyebabkan perubahan yang signifikan pada peran ibukota Kesultanan Deli. Kajian berikut ini bertujuan untuk menjelaskan perubahan peranan yang dimainkan oleh ibukota Kesultanan Deli sebelum dan sesudah perpindahan. Hasil kajian sendiri diharapkan dapat berkontribusi positif dalam menyumbang pengetahuan mengenai sejarah kesultanan-kesultanan di Nusantara. Adapun metode yang dipergunakan dalam kajian ini adalah metode penelitian literatur. Hasil kajian menunjukkan bahwa ibukota Kesultanan di Labuhan memainkan peran yang lebih kompleks daripada ibukota yang berada di Sultandgrond. Labuhan bukan hanya berperan sebagai pusat pemerintahan Kesultanan Deli melainkan juga pusat ekonomi dimana pelabuhan ekspor dan impor Deli juga berada disana. Sementara itu, setelah perpindahan ibukota ke Sultangrond di Medan, ibukota Kesultanan Deli tidak lagi memainkan peran sebagai pusat ekonomi seperti sebelumnya. Kata kunci: Kesultanan Deli, sejarah Islam, Labuhan, Sultangrond, Pantai Timur Sumatera